(untitled) (Nigerian Journal of Technology, 2002)
Many rotating machines operate over a range of speeds. It is therefore of practical interest in machine condition monitoring to see if there is a relationship between the speed at which diagnostic inspection is carried out and the early detection of incipient defect in the machine. In this paper, the effect of operating speed in the early detection of incipient defect in a Seta mechanism is investigated using a number of techniques. It is shown that for-an analysis bandwidth optimum for incipient defect detection, the detection sensitivity is improved if the diagnostic inspection of the mechanism is carried out at lower rather than higher speeds.